A novel type of tubular structure with auxeticity both in radial direction and wall thickness. (June 2021) - Zhang, Xiang Yu; Wang, Xin Yuan; Ren, Xin; Xie, Yi Min; Wu, Yao; Zhou, Yi Yi; Wang, Shi Long; Han, Chuan Zhen
Abstract: A novel type of tubular structure has been proposed in this paper, which is the first tubular structure with auxeticity in the wall thickness as well as in the radial direction. This tubular structure exhibits good stability under axial compression. The most innovative feature is that its inner diameter and outer diameter have opposite deformation directions. When axially compressed (stretched), its outer diameter will become smaller (larger) while its inner diameter will become larger (smaller). Besides, its closed surfaces of tube wall can broaden its applications in the fields of civil engineering and mechanical engineering. The accuracy of the finite element model was verified by comparison between experiments and numerical analysis. Deformation characteristics of tubular models generated by offset method and rotation method were studied. The influence of cell layers, PSF (Pattern Scale Factor) value and t/R (the ratio of wall thickness t to diameter R) value was also studied by parametric analysis. Highlights: A novel type of tubular structure with auxeticity both in the radial direction and wall thickness has been proposed. The generation method and geometrical characteristics of the tubular structure are introduced in detail. The influences of cell layers, PSF value and t/R value on the tubular structure are analyzed.